Construção e validação de instrumento para consulta de enfermagem às pessoas com infecções sexualmente transmissíveis - Guedes, Dayse da Silva (2017)
The application of a scientific instrument allows the professional to improve the quality of care management and the planning of their activities, besides serving as a guide for their actions. Considering the lack of a validated instrument in the national and international literature that can assist the nurse in the consultation of the population with sexually transmitted infections, it is necessary to expand technologies that may facilitate the work of the professionals who work in the prevention, control and treatment of this type of health problem. The objective of this study is to describe the process of construction and validation of an an instrument’s contents to be used during the nursing visit to people with sexually transmitted infections. This is a methodological study conducted from March 2016 to November 2017, based on the Clinical Protocol and Therapeutic Guidelines for Integral Care for People with Sexually Transmitted Infections (2015), of the Ministry of Health and the clinical indicators found in the literature, following the theoretical reference of Self-care proposed by Dorothéa Orem. After the construction of the instrument, the validation process was carried out by 44 teaching / research and assistance specialists. The data were compiled and the Content Validity Index was calculated by means of a Likert scale, which evaluates the agreement of the expert on a particular aspect. Thus, items that obtained IVC ≤ 0.85 were excluded or modified, according to the experts' suggestions. In addition, a proportional test was performed for the purpose of comparison among groups of specialists. The instrument developed contains 18 subdivisions and presented a General Content Validity Index of 97% agreement between the answers for relevance, and 99% for clarity and comprehension being considered excellent. In addition, the experts contributed positively, developing suggestions that made it possible to adjust the inappropriate issues. The use of this nursing consultation model, with subsidy in a theory of high importance, such as the Orem Theory, for nursing care, can contribute significantly to the orientation of care provided by nurses to people with sexually transmitted infections , in benefit of the quality of care, contributing to the promotion of the health of the users. The constructed instrument represents the initial step in search of a systematized assistance that contemplates an integral approach of care to these patients.